2013
DOI: 10.1128/jb.02210-12
|View full text |Cite
|
Sign up to set email alerts
|

HipA-Triggered Growth Arrest and  -Lactam Tolerance in Escherichia coli Are Mediated by RelA-Dependent ppGpp Synthesis

Abstract: Persistence is a phenomenon whereby a subpopulation of bacterial cells enters a transient growth-arrested state that confers antibiotic tolerance. While entrance into persistence has been linked to the activities of toxin proteins, the molecular mechanisms by which toxins induce growth arrest and the persistent state remain unclear. Here, we show that overexpression of the protein kinase HipA in Escherichia coli triggers growth arrest by activating synthesis of the alarmone guanosine tetraphosphate (ppGpp) by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
95
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 54 publications
(55 reference statements)
8
95
0
Order By: Relevance
“…2B) (27). Moreover, HipA also failed to induce (p)ppGpp synthesis in a ΔrelA strain (31), consistent with the fact that HipA-mediated persistence indeed depends on the activation of the stringent response in E. coli (27,28,31).…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…2B) (27). Moreover, HipA also failed to induce (p)ppGpp synthesis in a ΔrelA strain (31), consistent with the fact that HipA-mediated persistence indeed depends on the activation of the stringent response in E. coli (27,28,31).…”
Section: Resultsmentioning
confidence: 56%
“…Previously, we and others established that persistence mediated by HipA correlates with the activation of the stringent response (27,28,31). Indeed, (p)ppGpp sharply increased by over 10-fold after hipA induction ( Fig.…”
Section: Resultsmentioning
confidence: 57%
“…Using a protocol modified from ref. 61, an isocratic method was developed to isolate the ppGpp peak on an Agilent Technologies 1200 series HPLC. The buffer consisted of 0.85 M ammonium phosphate, pH 2.1.…”
Section: Methodsmentioning
confidence: 99%
“…It was suggested that free Hip toxin increases the level of ppGpp, thereby leading to altered gene expression and thus priming cells for the phenotypic switch (131). More recently, overexpression of HipA was shown to trigger growth arrest by inducing RelA-medi-ated synthesis of ppGpp (132). Suppression of ppGpp synthesis by use of chloramphenicol relieves Hip-mediated inhibition of DNA replication, thereby restoring vulnerability to ␤-lactam antibiotics (132).…”
Section: Persisters Play a Central Role In Biofilm Recalcitrance Towamentioning
confidence: 99%
“…More recently, overexpression of HipA was shown to trigger growth arrest by inducing RelA-medi-ated synthesis of ppGpp (132). Suppression of ppGpp synthesis by use of chloramphenicol relieves Hip-mediated inhibition of DNA replication, thereby restoring vulnerability to ␤-lactam antibiotics (132).…”
Section: Persisters Play a Central Role In Biofilm Recalcitrance Towamentioning
confidence: 99%